2018
DOI: 10.1007/s10072-018-3306-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant default mode network in amnestic mild cognitive impairment: a meta-analysis of independent component analysis studies

Abstract: Independent component analysis (ICA) is one of the most popular and valid methods to investigate the default mode network (DMN), an intrinsic network which attracts particular attention in amnestic mild cognitive impairment (aMCI). However, previous studies present inconsistent results regarding the topographical organization of the DMN in aMCI. Therefore, we conducted a quantitative, voxel-wise meta-analysis of resting-state ICA studies using Seed-based d Mapping to establish the most consistent pattern of DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…These regions of ReHo alterations are critical hubs of the DMN [ 33 ]. The DMN, which is implicated in self-referential and memory processing, is the most studied brain cognitive network in aMCI and AD because it is preferentially susceptible to neurodegeneration and involves early in the AD pathophysiology [ 33 , 34 ]. Convergent evidence suggests that remote functional connectivity in the DMN in AD and aMCI is reorganized, which correlates with cognitive impairments [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These regions of ReHo alterations are critical hubs of the DMN [ 33 ]. The DMN, which is implicated in self-referential and memory processing, is the most studied brain cognitive network in aMCI and AD because it is preferentially susceptible to neurodegeneration and involves early in the AD pathophysiology [ 33 , 34 ]. Convergent evidence suggests that remote functional connectivity in the DMN in AD and aMCI is reorganized, which correlates with cognitive impairments [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging research has changed this view substantially, as these areas include the posterior cingulate cortices, which have been linked to the DMN, 1,2 a large scale, restingstate network, whose dysfunction has been linked to numerous brain diseases. [12][13][14][15][16][17] Furthermore, graph theoretical analyses have suggested that the PCC areas are among the highest functionally connected clusters of brain regions in the cerebrum. 18 Our data support this view, as the functional connectivity maps of some of these areas involve a large number of spatially and functionally OPERATIVE NEUROSURGERY…”
Section: Discussionmentioning
confidence: 99%
“…The precuneus, cingulate gyrus, and middle temporal gyrus are parts of the default mode network (DMN) [26]. The DMN is usually active during rest and is suspended or weakened when engaged with the external environment [27,28]. The DMN is generally the primary network affected by chronic pain [29].…”
Section: The Default Mode Networkmentioning
confidence: 99%